Characterisation of the bacterial and archaeal microbiota in fresh colostrum collected from a single, spring-calving dairy herd - Sabine Scully; Bernadette Earley; Paul E. Smith; Matthew S. J. Finnie; Catherine McAloon; Frank Buckley; David A. Kenny; Sinéad M. Waters (PLoS ONE, 2025)
There is increasing evidence to support the existence of a naturally occurring colostral microbiome, which may influence the development of the gastrointestinal microbiota and immune function of the calf. The objective of this study was to characterize the prokaryotic community of colostrum collected fresh (within 2h parturition) from primi- and multiparous Holstein-Friesian (n = 17) and Jersey (n = 10) cows. Extracted microbial DNA underwent qPCR and Illumina amplicon sequencing of the V4 region of the 16S rRNA gene. High throughput amplicon sequencing data was analysed using a variety of R packages. Taxonomy was assigned using the SILVA database (v. 138.1). No effect of breed or parity was observed on alpha (α; Shannon) diversity and community composition. The mean Shannon score was 3.33 (SE 0.14), indicating a diverse community within sample. A total of 681 genus-level amplicon sequence variant (ASV) groups were identified prior to filtering for relative abundance (RA) of >0.05%. Nineteen bacterial genera were identified as core. The predominant bacterial phyla observed were Bacillota, Pseudomonadota, and Actinomycetota . Community membership consisted of common gut commensals, with many members exhibiting diverse metabolic functions. Within the archaeal community, Methanobrevibacter had the highest RA , accounting for 85.99%. No observed differences between breeds suggests that farm origin may be more influential than breed on microbiota composition. The presence of archaea and strict anaerobes highlights the need to investigate the existence of an entero-mammary pathway in cattle. This is the first study jointly characterising bacteria and archaea in colostrum from different breeds from the same dairy herd under pasture-based conditions. The diverse bacterial community observed warrants further investigation into its role in calf health in early life. Specific microbes, like Lachnospiraceae , should be investigated for their potential in the development of probiotics and preventative practices for better calf health.